Religious Moderation-Based Islamic Education Model by Nahdlatul Ulama at Islamic Boarding Schools in Lampung Province - Wasehudin, Wasehudin; Syafei, Imam (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
Nahdlatul Ulama (NU) has made a substantial contribution to Islamic education, especially in the world of Islamic boarding schools. Islamic boarding schools have a significant influence in creating intelligent and great young generations. The focus of this study is to analyze the implementation and the results of Islamic education based on religious moderation in Islamic boarding schools in Lampung province. The Islamic boarding schools that served as objects of study are Islamic boarding schools in Lampung province that have implemented religious moderation, namely the Ushuluddin Islamic Boarding School in South Lampung, Al-Hikmah Islamic Boarding School Bandar Lampung, Al-Hidayat Islamic Boarding School Pesawaran, and Raudhatu Sholihin Islamic Boarding School Central Lampung. This study applied the field research design with a qualitative descriptive approach. The data were collected through observation, interviews, and documentation. The study results show that Islamic boarding schools in Lampung province have implemented Islamic education based on religious moderation. Islamic boarding schools in Lampung province have similarities in terms of application, namely Tawasuth (taking the middle way) and Tsamuh (tolerance). They also integrate the general curriculum and religious curriculum by studying the Kitab Kuning (Kitab Turath), yasinan, Tabligh Akbar, room placement based on ethnic background, and Bahtsul Masail activities. As a result, the students have a strong base of thought and character by openly responding to differences and thinking.